Abnormal Expressions of DNA Glycosylase Genes NEIL1, NEIL2, and NEIL3 Are Associated with Somatic Mutation Loads in Human Cancer. (3rd March 2016) - Shinmura, Kazuya; Kato, Hisami; Kawanishi, Yuichi; Igarashi, Hisaki; Goto, Masanori; Tao, Hong; Inoue, Yusuke; Nakamura, Satoki; Misawa, Kiyoshi; Mineta, Hiroyuki; Sugimura, Haruhiko
Abstract : The effects of abnormalities in the DNA glycosylases NEIL1, NEIL2, and NEIL3 on human cancer have not been fully elucidated. In this paper, we found that the median somatic total mutation loads and the median somatic single nucleotide mutation loads exhibited significant inverse correlations with the median NEIL1 and NEIL2 expression levels and a significant positive correlation with the median NEIL3 expression level using data for 13 cancer types from the Cancer Genome Atlas (TCGA) database. A subset of the cancer types exhibited reduced NEIL1 and NEIL2 expressions and elevated NEIL3 expression, and such abnormal expressions of NEIL1, NEIL2, and NEIL3 were also significantly associated with the mutation loads in cancer. As a mechanism underlying the reduced expression of NEIL1 in cancer, the epigenetic silencing of NEIL1 through promoter hypermethylation was found. Finally, we investigated the reason why an elevated NEIL3 expression level was associated with an increased number of somatic mutations in cancer and found that NEIL3 expression was positively correlated with the expression of APOBEC3B, a potent inducer of mutations, in diverse cancers. These results suggested that the abnormal expressions of NEIL1, NEIL2, and NEIL3 are involved in cancer through their association with the somatic mutation load.